PEMAKNAAN DAN KONSEKUENSI BUDAYA TATO PADA SUKU DAYAK - Sia, Elok Feni; Yunanto, Taufik Akbar Rizky (Universitas Muhammadiyah Jember, 2019)
Dayak Tribe were originally from immigrants from the Yunnan region of southern China and traveled on the island of Borneo. Dayak tribe itself has a culture of signs or symbols where each motif and placement of tattoo have different meanings and can also be done carelessly. According to the belief that black tattoo will turn into a pathway to eternity after they die, the tattoo is a spiritual aspect and inheritance that is in accordance with the Dayak tribe and tattoo can also symbolize high identity and social status. This goal is to find out the meaning and understanding of tattoo culture in Dayak tribe. According to Throndike, behavioristic learning theory emphasizes consideration in terms of (Readiness Law), (Exercise Law), (Influence Law). A pleasant consequence would be to improve tattooing behavior, if the individual is ready to meet the procedures and prerequisites for tattooing the individual will continue to train him then receive the pleasant and acceptable because he can tattoo.